Evolution of the Beaches in the Regional Park of Salinas and Arenales of San Pedro del Pinatar (Southeast of Spain) (1899–2019) - Daniel Ibarra-Marinas; Francisco Belmonte-Serrato; Gustavo A. Ballesteros-Pelegrín; Ramón García-Marín (ISPRS International Journal of Geo-Information, 2021)
Coastal erosion is anissuewhich affects beaches all over the world and that signifies enormous economic and environmental losses. Classed as a slow phenomenon, the evolution of the coastline requires long-term analysis. In this study, old cartography and aerial photographs from various dates have been used to study the evolution of the coastline. The information has been processed with free software (QGIS) and for the calculation of sediment transport the Coastal Modeling System (SMC) software. The results show the accretion/erosion phenomena that occurred after the construction of the port in San Pedro del Pinatarin 1954 and which changed the coastal dynamics of a highly protected area. In some sectors, the beach has been reduced almost in its entirety, with retreat rates of up to −2.05 m per year and a total area loss of 66,419.81 m2 in Las Salinas beach and 76,891.13 m2 on Barraca Quemada beach.